Analisis Biaya Pengeringan Benih Padi (oryza sativa) Di PT. Sang Hyang Seri (persero) Kantor Cabang Asahan - Harapan Panjaitan; Zulkifli Lubis; Syaifuddin Syaifuddin (Universitas Medan Area, 2018)
Cost Analysis of Seed Drying Rice (Oryza sativa) in PT. Sang Hyang Seri (Persero) Branch shavings. PT. Sang Hyang Seri (Persero) Branch shavings used as the study site because here is a branch that has a rice seed breeding area under study and activities are drying by the method referred to in the study. This study uses field observations using a questionnaire and interview research instruments, this kind of research is descriptive quantitative. The population in this study were all employees and unit leader drying rice seeds PT. Sang Hyang series (Persero) Branch shavings. The model used data analysis is descriptive and quantitative analysis. To test for differences in the cost of drying rice seeds used analysis of different test-score score (T test) with the help of software SPSS version 17. The results of this study are: 1) There is no significant difference in the cost of drying method of drying floor open (natural) plain rice and rice seed Ciherang candidate, Mekongga and PB There is a significant difference 42. cost of drying method of drying floor open (natural) plain rice and prospective rice seed varieties Impari 13. 2) there is no significant difference method box dryer drying costs and potential ordinary paddy rice seed Ciherang, Mekongga and Impari 13. there were significant differences in the cost of drying method box dryer ordinary rice and rice seed varieties candidate PB 42. 3) There are significant differences drying costs and the open method of drying floor box dryer ordinary rice and rice seed Ciherang candidate, Mekongga and Impari 13. Keywords : Rice Seeds, Dryer